Architecture of Peace in Ambon: Reading Dynamics of Peace After Ten Years of Conflict - Saidin Ernas (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
The dynamics of peace in Ambon have been getting stronger during the last ten years, but to what extent this phenomenon can be considered as a solid basis for peace, would require a critical analysis. This paper is the result of field research on peace in Ambon using the theory of